2020
DOI: 10.1039/d0ra04015k
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost electrochemical detection of l-tyrosine using an rGO–Cu modified pencil graphite electrode and its surface orientation on a Ag electrode using an ex situ spectroelectrochemical method

Abstract: A low cost reduced graphene oxide–copper hybrid nano thin-film modified pencil graphite electrode has been employed to detect the l-tyrosine enantiomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Due to the electric double layer (EDL) mechanism, fast charge/discharge processes, and higher ohmic resistance, the oxidation peak current (Ip) of Tyr increases as the potential scan rate increases (Figure 5a). The oxidation peak also shifts from 670 mV to a more positive potential of 710 mV, typical of irreversible surface controlled electrochemical processes [36]. A linear relationship between the Ip and the square root of the scan rate (v 1/2 ) has also been demonstrated (Figure 5b), indicating diffusion-controlled reaction kinetics: Ip = 3.57 ν 1/2 (mV s -1 ) -9.1531 (R 2 = 0.9833) (…”
Section: Effect Of Scan Ratementioning
confidence: 98%
See 2 more Smart Citations
“…Due to the electric double layer (EDL) mechanism, fast charge/discharge processes, and higher ohmic resistance, the oxidation peak current (Ip) of Tyr increases as the potential scan rate increases (Figure 5a). The oxidation peak also shifts from 670 mV to a more positive potential of 710 mV, typical of irreversible surface controlled electrochemical processes [36]. A linear relationship between the Ip and the square root of the scan rate (v 1/2 ) has also been demonstrated (Figure 5b), indicating diffusion-controlled reaction kinetics: Ip = 3.57 ν 1/2 (mV s -1 ) -9.1531 (R 2 = 0.9833) (…”
Section: Effect Of Scan Ratementioning
confidence: 98%
“…This decrease in sensitivity is likely due to saturation of the electro-catalytic ability of the GO-CS-SPCS and kinetic limitation [36,55].…”
Section: E Electrochemical Determination Of Tyr Using Dpvmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual voltamperometric methods used for L-Tyr detection reported in the literature are differential pulse voltammetry [ 34 ], cyclic voltammetry [ 35 , 36 ], chronoamperometry [ 37 ], linear sweep voltammetry [ 38 , 39 ], and square wave voltammetry [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported PPy doped with sodium dodecyl sulfate (SDS), potassium hexacyanoferrate (II) (FeCN), sodium Nitroprusside (NP), dodecylbenzene sulfonate (DBS), and p-toluene sulfonate (PTS) in different organic solvents or in aqueous environments, which could lead to high performances, respectively high conductivity, high thermic stability, reproducibility, etc. [ 34 , 35 ]. One advantage of electrochemical synthesis is the possibility of carrying out the deposition on the electrode and the doping of the polymer in one stage, a procedure useful in the case of electrochemical sensor development [ 46 ].…”
Section: Introductionmentioning
confidence: 99%